EFL Students’ Attitude Toward the Use of Local Languages in Daily Life and Learning Environment - Sholihah, Lilis; Flora, Flora; Widodo, Mulyanto; Maydiantoro, Albet; Hariri, Hasan (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study investigates the attitudes of English as a Foreign Language (EFL) students toward the use of local languages in daily life and learning environments within the multilingual context of Lampung, Indonesia. Despite Indonesia’s linguistic diversity, empirical evidence on language attitudes and local language shift at the university level remains limited, particularly in non-metropolitan regions. Adopting a qualitative case study design, data were collected from 54 undergraduate EFL students through open- and closed-ended questionnaires. Participants were selected using purposive sampling to represent diverse ethnic backgrounds. The data were analyzed thematically through coding and pattern identification, supported by descriptive statistics. The findings indicate a strong dominance of Bahasa Indonesia as the primary language of communication and perceived mother tongue, even among students from Lampungese and Javanese backgrounds. Local language proficiency was generally low, with many students demonstrating only passive understanding or no proficiency at all. Although participants expressed positive attitudes toward the cultural importance of local languages, actual use was constrained by limited intergenerational transmission, low social prestige, and the influence of globalization. This study highlights ongoing local language shift among university EFL learners and underscores the need for educational strategies that integrate local languages into formal learning contexts to support linguistic diversity and cultural sustainability.